The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3906/sag-1804-62
|View full text |Cite
|
Sign up to set email alerts
|

Paricalcitol inhibits the Wnt/beta-catenin signaling pathway and ameliorates experimentally induced arthritis

Abstract: Background/aim: The Wnt/β-catenin pathway has important biological activities, including the differentiation of cells and joint formations. The aim of our study was to determine the effect of paricalcitol on experimentally induced arthritis. Materials and methods: Type II collagen combined with Freund's adjuvant was applied to induce arthritis in Wistar albino female rats. Paricalcitol (0.3 µg/kg daily) was subcutaneously injected starting 1 day after collagen applications (prophylactic group) or 1 day after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…39 Others have reported that the inhibition of the Wnt/b-catenin signaling pathway caused by paricalcitol can ameliorate RA. 40 In a previous study of osteosarcoma, the knockdown of HOTTIP was demonstrated similarly to suppress cell proliferation and promote cell apoptosis via inhibiting the Wnt/b-catenin signaling pathway. 41 Together with our results, it appears evident that HOTTIP can inhibit SFRP1 and activate the Wnt signaling pathway by mediating Dnmt3b, thereby upregulating the levels of inflammatory factors and RA marker genes.…”
Section: Discussionmentioning
confidence: 94%
“…39 Others have reported that the inhibition of the Wnt/b-catenin signaling pathway caused by paricalcitol can ameliorate RA. 40 In a previous study of osteosarcoma, the knockdown of HOTTIP was demonstrated similarly to suppress cell proliferation and promote cell apoptosis via inhibiting the Wnt/b-catenin signaling pathway. 41 Together with our results, it appears evident that HOTTIP can inhibit SFRP1 and activate the Wnt signaling pathway by mediating Dnmt3b, thereby upregulating the levels of inflammatory factors and RA marker genes.…”
Section: Discussionmentioning
confidence: 94%
“…Considering the role of cellular immune function in RA patients and the differentiation of CD4 + T cells into Th17 cells for the development of RA, 14 , 24 , 26 the effects of the serum-derived exosomes of RA patients on CD4 + T cell proliferation, apoptosis, and Th17 differentiation were analyzed. The result indicated that serum-derived exosomes from RA patients promoted proliferation of CD4 + T cells ( Figure 2a ) and inhibited CD4 + T cell apoptosis in RA patients ( Figure 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…25 Wnt/ β-catenin inhibition was shown to alleviate RA. 26 In light of previous studies, we determined the impact of serum-derived exosome containing NEAT1 in RA through regulation of the miR-144-3p/ROCK2/Wnt/β-catenin axis.…”
Section: Introductionmentioning
confidence: 99%
“…38 Paricalcitol, a synthetic analog of vitamin D, modulates the Wnt pathway by reducing expression of Axin2, Wnt5a , and DKK1. 39 Collagen-induced arthritis rats treated with paricalcitol once a day for 17 days via subcutaneous injection had less cartilage and subchondral bone destruction, reduced perisynovial inflammation, and significantly lower arthritis scores at 29 days compared with sham-injected arthritic rats. 39 Finally, the natural microbial extracellular heteropolysaccharide Xanthan gum inhibits the Wnt pathway by suppressing expression of downstream genes MMP13 and ADAMTS5.…”
Section: Preclinical Genetic Studiesmentioning
confidence: 91%
“…39 Collagen-induced arthritis rats treated with paricalcitol once a day for 17 days via subcutaneous injection had less cartilage and subchondral bone destruction, reduced perisynovial inflammation, and significantly lower arthritis scores at 29 days compared with sham-injected arthritic rats. 39 Finally, the natural microbial extracellular heteropolysaccharide Xanthan gum inhibits the Wnt pathway by suppressing expression of downstream genes MMP13 and ADAMTS5. 40 IA administration of Xanthan gum to DMM-induced OA rabbits once weekly for 5 weeks restored articular cartilage, significantly lowered OARSI scores, and reduced cartilage damage compared with saline-injected OA controls.…”
Section: Preclinical Genetic Studiesmentioning
confidence: 91%